Are they publishing? A descriptive crosssectional profile and bibliometric analysis of the journal publication productivity of Italian physiotherapists (Archives of Physiotherapy, 2018)
Background: In a clinical science-based profession such as physiotherapy, research is mandatory to update knowledge and to provide cost-effective, high quality treatments. This study aimed to provide point prevalence of Italian physiotherapists who are academics, holding a PhD degree, or being authors of scientific papers. The scientific journal productivity of physiotherapists was also thoroughly analyzed. Methods: A descriptive cross-sectional study was carried out on all Italian physiotherapists. Academics, postdoctoral research fellows, and PhD graduates were identified by searching the Italian Ministry of Education, University and Research (MIUR), Italian Society of Physiotherapy, and university websites. Then, authors of articles indexed in Scopus were searched. The following data were extracted: type of affiliation, authorship order, H-index, number of publications and citations, name of journals, year of publication, and journal’s Impact Factor. Results: The prevalence of academics, physiotherapists holding a PhD, or being author was 0.01%, 0.05%, and 0.56%, respectively. We identified 1083 papers co-authored by Italian physiotherapists, and their number has progressively increased over the years (p < 0.001). There was a significant difference between researchers and clinicians in both publication productivity (p < 0.01), citations (p < 0.01), and H-Index (p = 0.05). Articles were published in 359 different journals, receiving a total of 13,373 citations. Conclusions: Despite the low prevalence of faculty members and the reduced availability of PhD programs in Italy (forcing some students to study abroad), the quantity and quality of journal productivity is growing fast, and an increasing number of physiotherapists are involved in research activities.
Keywords: Bibliometrics; Authorship; Scientific output indicators